The Role of Biologics in Chronic Rhinosinusitis With Nasal Polyps - Patel, Gayatri B. (Ear Nose Throat J, 2020)
Biologic therapy is a new treatment option for patients with chronic rhinosinusitis with nasal polyps (CRSwNP). Currently, the only biologic with Food and Drug Administration–approval status for CRSwNP is dupilumab. Several other biologics are likely to be approved for CRSwNP, including mepolizumab and omalizumab, based on their promising phase 3 trial results. The role of biologics in the treatment paradigm requires consideration of multiple factors that have yet to be clearly established. This includes identifying patients most appropriate for biologic therapy while considering long-term safety and cost-effectiveness in the context of patient preferences and goals.